Pelatihan Pemanfaatan Digital Marketing dan Strategi Packaging untuk Meningkatkan Consumer Buying Interest pada UMKM Binaan Rumah Kurasi di Desa Joho Semen Kediri: Training on the Utilization of Digital Marketing and Packaging Strategies to Increase Consumer Buying Interest in MSMEs Fostered by Rumah Curasi in Joho Semen Village, Kediri - Aysa, Imma Rokhmatul; Sutantri, Sutantri; Mala, Iva Khoiril; Fattah, Fuad Abdul; Lestari, Dewi Ayu Intan; Husna, Murni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Community Service was carried out by a team of lecturers from the Faculty of Sharia and Economics, UIT Lirboyo Kediri, and the Faculty of Economics and Business, Universitas Negeri Malang, and students of the Sharia Banking Study Program, Faculty of Sharia and Economics, UIT Lirboyo Kediri, which was carried out in Joho Village, Semen District, Kediri Regency. Targeting UMKM actors. The main objective of this activity is to improve skills in the economic field, especially digital marketing and packaging of UMKM products. This mentoring activity was carried out through a workshop that was held for several days, targeting UMKM actors of approximately 24 participants. The workshop material consisted of literature about digital marketing, including marketing strategies that study how to promote products through digital media to reach consumers quickly, precisely, personally, and relevantly. Material on product packaging includes processes related to designing and manufacturing containers or wrappers to protect a product. The obstacles faced in this mentoring include the lack of education about digital marketing, product packaging, and internet networks, and they only rely on offline sales, so product sales are not yet widespread. It is expected that with this assistance, the ability of MSME actors in digital marketing and product packaging strategies will increase.